SHOULD THE FLAG FIT, OR MUST WE ACQUIT? (The Pretoria Student Law Review, 2021)
This paper is written in response to recent litigation before the Equality Court concerning the old South African flag.3 Following alleged gratuitous displays of the flag, the Nelson Mandela Foundation in February 2018 announced that it had made an application to the Equality Court for an order declaring the flag’s gratuitous display as, inter alia, hate speech.4 The declaration sought would arguably make for a limitation on one’s right to freedom of expression. Accordingly, I assess the relief sought by the Nelson Mandela Foundation by evaluating: (1) whether conceptually hate speech prohibitions are legitimate; (2) whether section 10 of PEPUDA passes constitutional muster; and (3) whether the flag can be outright classified as hate speech under PEPUDA.
Keywords: Equality Court; old South African flag; Nelson Mandela Foundation; gratuitous display; hate speech; right to freedom of expression; PEPUDA